P-290 Sibling oocytes from the same cohort to compare embryo culture in dry versus humidified incubators: report on KPIs and clinical outcome. (30th June 2022) - Marti Vilanova, M; Jaldo Garcia, J; Gonzalez Marti, B; Pessah, C; Entezami, F
Abstract: Study question: Do embryo culture key point indicators (KPIs) and clinical outcome differ according to the type of incubator; humidified versus dry. Summary answer: Embryo culture in both type of incubators yields the same KPIs and clinical outcome. What is known already: Lately, dry incubators have been introduced for optimized embryo culture thanks to their small size, fast gas replenishment rate, and lower risk of bacterial/fungal contamination. Nonetheless, it has previously been reported that embryo culture in dry incubation system could compromise embryo development by increasing apoptosis, due mainly to increase in the osmolality of the medium by evaporation. Few studies have shown reduced implantation and ongoing pregnancy rates (OPR) when the culture was performed in dry incubators compared to humidified ones. To compare the incubation systems, the oocyte cohorts were entirely assigned to the study group or to the control group. Study design, size, duration: A prospective observational study at the American Hospital of Paris included 141 patients and 143 cycles during 2020-2021 . Patients were selected on the exclusive basis of strict male factor and use of ejaculated sperm to avoid bias through oocyte quality variation due to associated female factor. Sibling oocytes from the same patient and the same cohort were assigned to be cultured in the same incubator, in an independent dry or humidified drawer. Participants/materials, setting, methods: A total of 1934 ovocytes were microinjected. Each half of the cohort was placed in multichamber AD-3100-CUBE (ASTEC, Japan) in independent humid and dry drawers. Fertlisation (FR) and lysis (LR) rates, top quality embryos at D2-D3 (TE2) (TE3), D5 blastulation (BR), top quality BR (TBR) and underrated BR (UBR) rates were recorded. After ultrasound guided SETs at D5, clinical outcome was verified. The groups comparisons were done by two tailed t-test and and Chi-square test. Main results and the role of chance: The mean female age at inclusion was 36.2± 5.2 and the mean number of mature oocytes was 6.8±2.6. A total of 1416 embryos were obtained at D3. No statistical differences were observed for the FR (72.0% in humid vs 73.0% in dry incubation, p  = 0.486), for TE2 (47.9% in humid vs 46.0% in dry incubation, p  = 0, 430) and for TE3 (45.9% in humid vs 41.6% in dry incubation, p  = 0, 145). Embryo fragmentation >50% was also compared in both groups on D2 and D3 but no statistical difference was observed (68.9% in humid vs 66.2% in dry incubation, p  = 0.783 for D2, and 66.0% in humid vs 59.6% in dry incubation, p  = 0.264 for D3). The overall BR was also similar in both groups. TBR was 60.0% in humid and 57.8% for dry incubation ( p  = 0.647), and the UBR was 39.9% in humid and 42.1% in dry conditions ( p  = 0.703). Finally, the clinical outcome was studied in both groups. A total of 91 single embryo transfers were performed from the humid embryo cohort and 78 from the dry embryo cohort. OPR and miscarriage rates were similar in both groups ( p  = 0.725 and p  = 0.468 respectively). As several pregnancies were still ongoing the live birth rates were not reported. Limitations, reasons for caution: Only fresh embryo transfers were taken in account. Cumulative PR and live birth rates should be further studied in order to confirm the lack of difference in clinical outcome between dry and humidified culture conditions Wider implications of the findings: In this study each patient was its own control group as the oocytes were splitted in the same incubator, in dry and humidified incubation. In opposite to other published studies we found similar KPIs of embryo culture in both groups and the clinical outcomes showed no statistical difference. Trial registration number: NA